Analysis and Comparative Study of Industral Design Patent Layouts of Automobile Manufacturers in Overseas Markets - Long, Yue; Ye, Xiaoxue; Wang, Jing (International Journal of Global Economics and Management, 2025)
In the context of globalization, the international development of the automotive industry has become an inevitable trend. As China has become the world’s largest automobile exporter, automotive companies are gradually shifting from product export to technology export. During this transition, the protection of industrial design patents, which are crucial for brand image and market competitiveness, becomes particularly important. This study focuses on the layout of industrial design patents, a key area of intellectual property in the automotive industry’s international expansion. It examines major global automotive markets and key regions for Chinese automotive brands’ international ventures. We selected 23 automotive manufacturers from the Fortune 2023 Global 500 list as research subjects and developed a comprehensive analysis system encompassing key indicators such as patent family size, number of authorized countries, and major countries/regions of patent layout. Through a co-linearity relationship network matrix and visual analysis using Gephi software, this study provides an in-depth analysis of the design patent layout of automotive companies. The aim is to offer robust theoretical support and practical guidance for the intellectual property strategy of Chinese automotive brands in the global market, further advancing their internationalization process.